Livelihood Transformation through the Existence of Mining and Tourism Industries: Case of North Halmahera District, North Maluku, Indonesia - Singgalen, Yerik Afrianto (Universitas Muhammadiyah Ponorogo, 2022)
Development has changed indigenous people's cultural structure and function, which is identical to a traditional lifestyle to the modern one, encouraging livelihood diversification or transformation. The development approach is vulnerable to socio-cultural, economic, and environmental changes, including in the mining and tourism sector. This article aims to describe the development process that has caused changes in the structure and function of indigenous culture and rural livelihoods in Northern Maluku, Indonesia. This study was done qualitatively using a case study approach to describe the livelihood strategies of indigenous people to cope with the existence of the mining and tourism industry’s activity in the North Halmahera Regency. The key informants involved in this research are traditional leaders, community leaders, and youth. Data collection is adjusted to the context of the research location, both around tourist destinations and mining areas. Data processing uses a triangulation approach. These findings indicate that the traditional community of Hibualamo had cultural structures and functions that mobilised access to social and natural capital. Furthermore, The challenges of globalisation cause a livelihood transformation and influence the capability of local communities to access financial capital, human capital, and physical capital.